(untitled) (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY Remote follow-up based on self-assessment plus a telephone call with a healthcare provider is a safe and reliable method for assessing the success of medical termination of pregnancy (mTOP) and can lead to an important reduction in costs. The aim of the study was to analyse its efficacy, acceptability and associated costs. METHODS This was a retrospective comparative study analysing two follow-up protocols for home-based mTOP. A total of 201 women were included: 56 for a standard in-clinic follow-up and 145 for a remote follow-up based on self-assessment with a low-sensitivity urine pregnancy test and a questionnaire. The main outcome was the total number of outpatient consultations needed for each procedure and the associated costs (according to the Swiss tariff system); acceptability and satisfaction were assessed using questionnaires. RESULTS Demand for home-based termination increased by 7.8% in the observation period. There was a reduction in diagnosis of retained products of conception, with a consequent decrease of follow-up consultations from 1.47 to 0.41 appointments per patient. A reduction of 38.9% in the average cost per patient (including supplementary follow-up appointments) was observed. Moreover, the remote alternative led to higher patient satisfaction (95.1% vs 55.0%) and acceptability (84.8%). The choice for long-acting reversible contraceptives was not affected by the removal of in-person consultation. CONCLUSION A remote follow-up procedure is an acceptable and less costly alternative to hospital-based follow-up with a higher rate of acceptability and adherence by the studied population.